4m-y=nform

Simple and best practice solution for 4m-y=nform equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4m-y=nform equation:


Simplifying
4m + -1y = nform

Solving
4m + -1y = fmnor

Solving for variable 'm'.

Move all terms containing m to the left, all other terms to the right.

Add '-1fmnor' to each side of the equation.
4m + -1fmnor + -1y = fmnor + -1fmnor

Reorder the terms:
-1fmnor + 4m + -1y = fmnor + -1fmnor

Combine like terms: fmnor + -1fmnor = 0
-1fmnor + 4m + -1y = 0

Add 'y' to each side of the equation.
-1fmnor + 4m + -1y + y = 0 + y

Combine like terms: -1y + y = 0
-1fmnor + 4m + 0 = 0 + y
-1fmnor + 4m = 0 + y
Remove the zero:
-1fmnor + 4m = y

Combine like terms: y + -1y = 0
-1fmnor + 4m + -1y = 0

The solution to this equation could not be determined.

See similar equations:

| 12+4x=8x-8 | | 1/2(8-6h)=5 | | 3x^2-12x+24y-48=0 | | 6-4x=7x-9x+4+2 | | C=15f+8h+5p | | 27x-2+47=180 | | 4z+6z=10 | | 27x-2=47 | | 4(x-3)+2=26 | | 7m+n=2forn | | 16x-8=14x+8 | | -3-(2-3x)=2x-(5-x) | | (3x-c)-5=x-7 | | 13-2n=-37 | | a+b(x-y)=cforx | | 20x+10=50 | | 2(x+4)-5(2x-1)= | | 11x-3=10x+5 | | n^2+n=6 | | 12-1.2(x-5)=22-2(5-3s) | | 2x+3/3=x-1/x-2 | | 3+(9n+5)=35 | | 5x+9x+2x+20=52 | | Ax+by=cforx | | n=300 | | 21-(x-5)=-4x+12 | | 3-7x=10-(x+1) | | 3/2u+3/8=5/4+9/2u | | 7+12x=115 | | 7+12x=105 | | 12x-(-2x+9)=26 | | 8u-6=9u-9 |

Equations solver categories